APLIKASI KOMPOSIT RESIN UNTUK PENATALAKSANAAN KEGOYANGAN GIGI AKIBAT TRAUMA - Venita Venita (Faculty of Dentistry, Universitas Indonesia, 2015)
Injuries to the teeth range from minor coronal fractures to total avulsion. If the injuries cause totl avulsion or luxation, there will be varying levels of injuries to the periodontal ligament, alveolus and microvascular supply. Management of the injured teeth ranges from inspection and treatment which includes stabilization by splinting. Usually splinting is accomplished by a segment of arch bar. Due to the ebsence of arch bar appliances, dentists often referred patients to an oral surgeon. It would cost extra time, for an immediate action to help the patients. This paper is a case report of a traumatized tooth which has been successfully stabilized with acid etched wire-composite. The use of composite resin is considered as a quick and an easy solution for dental trauma therapy.